MOM CARE: LEVERAGING INTELLIGENT SYSTEMS FOR COMPREHENSIVE MONITORING AND SUPPORT DURING PREGNANCY - Borhade, Siddhi; Doke, Gayatri; Bhujbal , Pratiksha; Said, Shubhangi (International Journal of Recent Advances in Engineering and Technology, 2025)
Maternal healthcare is critical for ensuring the well-being of pregnant women and their unborn children. Mom Care is an intelligent monitoring and guidance system designed to provide personalized maternal healthcare through real-time health tracking, emergency alerts, and pregnancy guidance. The system leverages cloud computing, user dashboards, and AI-based monitoring to ensure timely health insights. The user-friendly interface allows expecting mothers to track vital parameters, receive medical alerts, and access personalized recommendations. The proposed system integrates IoT-based health monitoring, AI-driven analysis, and a responsive user dashboard to enhance maternal healthcare accessibility and effectiveness.